From House Church to Tenement Church: Domestic Space and the Development of Early Urban Christianity—The Example of Ephesus - Billings, Bradly S. (The journal of theological studies, 2011)
Whilst the literary record points to the phenomena of the ‘house church’ in multiple localities across the Roman world, there is a paucity of archaeological evidence for houses large enough to accommodate the numbers involved, and no attested record of purpose-renovated or purpose-built meeting places until the third century. The application of a relatively new approach in the sociological investigation of ancient communities, known as social networking theory, may, however, enable us to understand the social circumstances under which communities were formed and cohered around a common cultic practice or figure in the ancient world. This in turn sheds light on the manner in which such groups formed, and adds to our knowledge of both the social and physical circumstances experienced by the first generations of urban Christians in the urban environments of the Greco-Roman city during the critical stage of the development of the group’s architecture, occupying the period c.50–150 ce. The possibility that the insula or apartment block may provide a suitable locale on both physical and social grounds is then discussed, appealing to both literary and archaeological evidence, using the city of Ephesus as a case study.